CFO techniques a hands-on guide to keeping your business solvent and successful - Guzik, Marina (Apress, 2012)
CFO Techniques: A Hands-on Guide to Keeping Your Business Solvent and Successful is a comprehensive and instructive working manual for multitasking chief financial officers and controllers working in the fast-paced commercial environment. Every senior financial professional with an ever-broadening span of control will benefit from this complete outline of the core activities—with specific descriptions of individual tasks—comprising the daily agenda of a successful CFO or controller. It covers everything from traditional responsibilities like budgeting and financial reporting, to more innovative tasks like performance analytics and business strategy development.